TUNJANGAN PROFESI GURU SEBAGAI UPAYA PENINGKATAN KOMPETENSI GURU DAN KARAKTER PESERTA DIDIK - Florentinus Minarta Nua (Universitas Islam Kadiri, 2020)
The presence of the 0.4 industrial revolution is a challenge for the education world. The education world must prepare professional teachers in accordance with their competencies so that they not only can produce students who excellent scientifically but also have a good character in accordance with national character. Provision of professional allowances is the choice of the government to improve teacher competence and the character of students. Unfortunately, there are still any contradiction regarding how big the role of professional allowance is increasing teacher competency. To answer this problem, researcher conducted in-depth observations through cross-site studies about improving teacher and student competency through the provision of professional allowances by using the technique of data analysis from Miles and Huberman. This study was conducted on teachers receiving professional allowance at the Mardi Wiayata education foundation in the city of Kediri which has two institutional sites, SMPK Mardi Wiyata and SDK Frateran 1. The results of this study illustrate that the Professional Allowance qualitatively can improve teacher competency so that it can also improve the character of students